Methodology for Assessment Energy Efficiency in the Industrial Sector - Neves, Fábio de Oliveira [UNESP] (2022)
Energy efficiency (E.E.) is vital for the technological development of a country, as it is intrinsically linked to the daily lives of people, public and private institutions, being a demand for national sovereignty, in addition to having enormous potential to avoid greenhouse gas emissions. However, the reduction of energy consumption has been decreasing, a trend that has important implications for consumers, companies and the environment. The increase in EE is linked to the type of sector and contribution, which is characterized by its intensity, as in the case of the industrial sector. Specifically, Brazil is currently the sixteenth country in industrial production, with a large part of its production coming from small and medium-sized companies. The absence of methodologies for EE assessment has driven a considerable part of the industrial sector to not have a safe direction in conducting the reduction of energy consumption. Thus, this thesis has as its central objective to build a metric to assist in the assessment of energy efficiency of small and medium-sized companies in Brazil. For that, using fuzzy logic, two analyzes were built to develop an assessment of the main priorities that the company should adopt. One measure is composed of a criticality index, which describe the company's main critical points considering aspects of environmental quality, cost management and industrial management in relation to EE measures, and the second by the technological improvement index that checks the main gaps of the predominant technologies of the production system: engine, lighting system, air conditioning, air compressor, refrigeration system, heating system, ventilation system, boilers and condensers. Seven case studies of companies from different industrial sectors were analyzed, in which an energy efficiency rating range was assigned through the criticality and improvement index. The analysis point out that most of the companies are within the critical range for aspects of industrial management and very inappropriate for improvement rates. In addition to these conclusions, the model indicated which actions should be taken for companies to complement or reach the energy consumption considered satisfactory. The developed model is an important tool for decision-making in small and medium-sized companies due to the different approaches contained in its structure.